Failure analysis on a ruptured petrochemical pipe - Mohd, Harun; Shaiful Rizam, Shamsudin; Azmi, Kamardin (Carl Hanser Verlag, 2010)
Link to publisher's homepage at http://www.materialography.net/index.php?id=1&L=1